Sasak language speech codes in various communication context: An ethnographic study by Dell Hymes - Mas'ud, Lalu; Fakihuddin, Lalu; Wijaya, Herman; Setiyoningsih, Titi (BAHASTRA, 2026)
This study reveals the use and negotiation of base alus (BA) and base jamaq (BJ) speech codes in the family, social, economic, and institutional spheres, and describes their sociopragmatic functions and the factors that influence their shifts. The method used was qualitative with an ethnographic approach to communication based on Dell Hymes' SPEAKING model. Data was collected through observation and interviews, analysed through reduction, presentation and conclusion drawing, and validated through triangulation and member checking. The results of the study found that BA persisted as a polite form of speech among the aristocracy in family and social circles. In the economic sphere, BJ–BA is chosen based on social status and closeness, while also regulating the "address of speech". In institutional settings, formal positions can transcend customary norms; the head of a jajar karang school is often addressed as BA, and interactions between teachers and the headmaster tend to use the BA form of address as a sign of respect. Among the younger generation, the use of BA has declined due to the influence of Indonesian and popular language, but it remains prevalent among aristocratic families and institutions that uphold politeness. This study reinforces communication ethnography by positioning code selection as a negotiation of relational power. The uniqueness of this study lies in its cross-domain mapping that links traditional hierarchy and professional hierarchy in the practice of speaking the Sasak language.